Impact of Prompting Agents on Task Completion in the Virtual World - Xie, Tao; Luo, Laiming (International Journal of Online and Biomedical Engineering (iJOE), 2017)
Based on a realized 3D virtual laboratory and virtual agents, this study was to investigate whether the virtual agents influence task completion. A total of 90 students participated in the experiment. They were evenly divided into three groups, one for the control group with no intervention and the other two for experiment groups with different interventional levels. The results show students who used the virtual agents worked much faster and more efficient than those who did not. The satisfaction of the experiment groups was superior to that of the control group. The correlation analysis showed a weak negative correlation between time in total and satisfaction (r = -.365), a strong positive correlation between speed and satisfaction (r = .626), and a strong negative correlation between time per task and satisfaction (r = -.685). However, correlation degree wasn't in concord with the interventional levels. This study suggests that virtual agents have promising effects on task completion and perceived satisfaction.